Characterisation of Minerals and Other Properties of Mukah Coal - Letchumanan, Shaktivell; Badarulzaman, Nur Azam; Seli, Hazman; Job Ajala, Amkpa (Journal of Advanced Mechanical Engineering Applications, 2023)
An increase in human population correlates with an increase in demand for energy. Coal has been a vital energy source for human populations for millennia, where it has played a major role in various industries, especially in the thermal-based industries. Coal is found in all three geographical provinces of Malaysia: Peninsular Malaysia, Sarawak, and Sabah. However, at most, the widespread and abundant occurrences of coal are found in Sarawak, especially in Mukah. The age of the coal deposits found in Mukah has instigated research that focuses mainly on the characterization of minerals and other properties in the coal, where those findings could be used to propose coal usage in other types of industries. To achieve those objectives, this research starts with a theoretical approach by discussing the coalification process, followed by understanding the types of coal produced from this process. Basic coal analysis, visual inspection, proximate analysis, XRD, SEM-EDX, and FTIR analysis were done to achieve all the objectives. At the end of the research, it was found that the Mukah coal sample is denser and has a higher gold content compared to the commercial coal sample. It was seen that the commercial coal possessed a high caloric value compared to the Mukah coal. This may be due to the high moisture and silicone content in the coal sample as it is mined directly from the earth. Overall, the Mukah coal sample could be used for other industries, like the fertilizer industry, rather than just being used to generate electricity by burning.